Issues for the international community 1978 - Gamani Corea (Intereconomics, 1978)
Progress in the restructuring of economic relations between developing and industrial countries has been insignificant in recent years and the current international economic situation is characterized by sluggishness of growth, intensifying protectionist pressures and persistent international monetary instability. Against this background the following article explains the tasks facing the international community in 1978 from UNCTAD's point of view.
Keywords: 330; UNCTAD